2023
DOI: 10.1111/ejss.13422
|View full text |Cite
|
Sign up to set email alerts
|

Stocktake study of current fertilisation recommendations across Europe and discussion towards a more harmonised approach

Suzanne Higgins,
Saskia D. Keesstra,
Žydrė Kadziuliene
et al.

Abstract: The European Commission has set targets for a reduction in nutrient losses by at least 50% and a reduction in fertiliser use by at least 20% by 2030, while ensuring no deterioration in soil fertility. Within the mandate of the European Joint Programme EJP Soil “Towards climate‐smart sustainable management of agricultural soils”, the objective of this study was to assess current fertilisation practices across Europe and discuss the potential for harmonisation of fertilisation methodologies as a strategy to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In relation to the target on 50% reduction in nutrient losses and 20% reduction in fertilizer use, the EJP SOIL EU‐wide stocktake (Higgins et al, 2021, 2023) found that there is a wide diversity in fertilization guidelines across Europe and a need for increased sharing of knowledge in terms of fertilization guidelines and analytical methods. Compared to mineral fertilization, the impacts of organic fertilizers on nutrients provision and SOM is much less known and needs to be investigated, accounting for the diversity of these amendments (manures, composts, digestates, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…In relation to the target on 50% reduction in nutrient losses and 20% reduction in fertilizer use, the EJP SOIL EU‐wide stocktake (Higgins et al, 2021, 2023) found that there is a wide diversity in fertilization guidelines across Europe and a need for increased sharing of knowledge in terms of fertilization guidelines and analytical methods. Compared to mineral fertilization, the impacts of organic fertilizers on nutrients provision and SOM is much less known and needs to be investigated, accounting for the diversity of these amendments (manures, composts, digestates, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Since natural gas is essential to the production of fertilizers, European producers are changing their methods, which may result in a halt or reduction in production. Gas price increases reduced Europe's supply of nitrogen fertilizer by 25% by September 2022 [61][62][63]. Even though the COVID-19 pandemic, climate change, and conflicts at first helped to reduce world hunger, undernourishment rose and now affects 10% of the world's population (828 million) in 2021, up from 8% (678 million) in 2019.…”
Section: Nanofertilizersmentioning
confidence: 99%
“…Fertilizer recommendations and decision support tools are important sources of information for farmers to increase nutrient use efficiency and decrease nutrient losses. Recent papers show that there is a large diversity in recommendations and tools between countries in the EU and that harmonization, shared learning, and a collective approach is recommended to tackle environmental problems (Nicholson et al, 2020;Higgins et al, 2023). The EU FAST tool (https://fastplatform.eu/) is developed for European Commission's DG Agriculture and Rural Development as nutrient management tool to support EU farmers, farm advisors, developers of digital solutions, and policy makers.…”
Section: Challenges For Farmersmentioning
confidence: 99%